Growth Pattern of Beauveria bassiana in Different Eco-friendly Media: Growth Pattern of Beauveria bassiana in Different Eco-friendly Media - Yadav, Sonam (International Journal of Pharmaceutical & Biological Archive, 2020)
Beauveria bassiana belongs to the class Deuteromycetes which is one of the important disease-causing biocontrol agents in insects. B. bassiana, formerly known as Botrytis bassiana (Balsamo), is a widely distributed soil inhabiting fungus. B. bassiana is also known to be best biocontrol agent against larval stage of the silkworm. B. bassiana is categorized as a white muscardine fungus due to the white color of sporulating colonies. It is a type of biopesticide which is based on entomopathogenic fungi which are often considerable scope as plant protection agents against several pathogens and insects including whiteflies, aphids, thrips, grasshoppers, and certain types of beetles. The present study deals with the use of different media such as coconut media, jaggery media, nutrient media, potato dextrose media, Sabouraud dextrose media, and molasses media.